2004
DOI: 10.1007/bf03218437
|View full text |Cite
|
Sign up to set email alerts
|

Size and uniformity variation of poly(MMA-co-DVB) particles upon precipitation polymerization

Abstract: Stable poly(methyl methacrylate-co-divinylbenzene) (poly(MMA-co-DVB)) microspheres were prepared by precipitation polymerization using acetonitrile as the main medium under various polymerization conditions, including modifications of the agitation speed, monomer and initiator concentrations, DVB content in the monomer mixture, and the use of various cosolvents. Gentle agitation was required to obtain smooth spherical particles. The individually stable microspheres were obtained at monomer concentrations of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
4
22
0
Order By: Relevance
“…The maximum yield of 70% in poly (AAm-co-DVB) with 75 mol % DVB in the precipitation polymerization was slightly lower than that of other copolymer systems such as poly(MMA-co-DVB) and poly(St-co-DVB), which showed 90 and 89%, respectively. 21,23 Because the yield of the polymerization was at maximum 70% in this system, the remaining 30% was confirmed to stay in the medium as a sol part.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…The maximum yield of 70% in poly (AAm-co-DVB) with 75 mol % DVB in the precipitation polymerization was slightly lower than that of other copolymer systems such as poly(MMA-co-DVB) and poly(St-co-DVB), which showed 90 and 89%, respectively. 21,23 Because the yield of the polymerization was at maximum 70% in this system, the remaining 30% was confirmed to stay in the medium as a sol part.…”
mentioning
confidence: 74%
“…[poly(MMA-co-DVB)], [20][21][22] and poly(styrene-co-divinylbenzene) [poly(St-co-DVB)]. 23 In addition, mechanistic studies to elucidate the formation of stable microspheres in the absence of any stabilizer have been reported 24,25 in which the absorption of oligomeric species onto the nuclei and the high degree of crosslinking are the primary reasons for the formation and stable growth of the microspheres.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Up today, the synthesis of highly crosslinked polymers using various self-crosslinkable monomers have widely been studied; poly(divinylbenzene) [P(DVB)], 15,16 poly(methacrylic acid-co-polyethylene oxide methyl ether methacrylate), 17 poly(methacrylate-co-DVB), 18 poly(chloromethyl styrene-co-DVB), 19 poly(DVB-co-maleic anhydride), 20 poly(methyl methacrylate-co-DVB), 8,21,22 poly(styrene-co-DVB) [P(St-co-DVB), 23 poly(acrylamide-co-DVB) 24 and poly(glycidyl methacrylate-co-DVB). 25,26 In addition, mechanistic studies to elucidate the formation of stable microspheres in the absence of any stabilizer have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…18 Furthermore, acetonitrile is reported to be the only solvent for preparing crosslinked polymer particles in the precipitation polymerization. 21,27 Much effort has paid to find other solvents instead of acetonitrile in the precipitation polymerization, which is one of expensive and environmentally unfriendly solvent. It was first reported that the stable P(St-co-DVB) spherical particles of 1.64~4.02 µm in diameter were prepared using acetone/methanol mixture medium and V-65 as an initiator at 53 o C in the precipitation polymerization.…”
Section: Introductionmentioning
confidence: 99%